Prävalenz und Indikatoren für Disstress bei Krebspatienten (Deutsche Zeitschrift für Onkologie, 2018)
Mehnert A et al. One in two cancer patients is significantly Disstressed: Prevalence and indicators of Disstress. Psycho-Oncology 2018; 27: 75–82